2022
DOI: 10.1039/d1fo03921k
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the serum metabolomic profiles of subjects with NAFLD in response to n-3 PUFAs and phytosterol ester: a double-blind randomized controlled trial

Abstract: Nonalcoholic fatty liver disease (NAFLD) has become the most common cause of chronic liver disease and threatens human health worldwide. As shown in our previous study, cosupplementation with phytosterol ester...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In the present study, we observed that a high dose of n -3 PUFA and n -6 PUFA supplementation increased the level of PC (32:3), and decreased the levels of PC (40:9), PC (42:10), and Cer-18:0. A previous study found that fish oil supplementation increased serum PC (35:5) and PC (36:5) levels and decreased PC (36:6) and PC (38:1) levels in patients with nonalcoholic fatty liver disease (NAFLD) [ 41 ]. Moreover, the C20:4n-6 enriched diet significantly decreased the hepatic levels of PC containing C18:2n-6 in mice compared with the control diet [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that a high dose of n -3 PUFA and n -6 PUFA supplementation increased the level of PC (32:3), and decreased the levels of PC (40:9), PC (42:10), and Cer-18:0. A previous study found that fish oil supplementation increased serum PC (35:5) and PC (36:5) levels and decreased PC (36:6) and PC (38:1) levels in patients with nonalcoholic fatty liver disease (NAFLD) [ 41 ]. Moreover, the C20:4n-6 enriched diet significantly decreased the hepatic levels of PC containing C18:2n-6 in mice compared with the control diet [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, statins can induce various adverse events including muscle disorders, liver dysfunction, kidney injury, and myocardial infarction (Cai et al, 2021). Some functional food, such as chickpeas (Mirizzi et al, 2019), wheat germ (Salehi‐Sahlabadi et al, 2022), and n‐3 polyunsaturated fatty acids (Ding et al, 2022) are used to prevent hepatic fat accumulation, thereby providing a potential way to ameliorate NAFLD. In this study, Bio‐A, one of the isoflavones in chickpea, reduced the intracellular TG content, inhibited ADRP expression, increased the expression of autophagosome formation biomarkers Beclin 1, LC3‐II, and ULK‐1 phosphorylation, and decreased the expression of p62, an autophagic flux biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Untargeted metabolomic analysis was performed using a UPLC-ESI-Q-TOF-MS system. 22 The raw data was processed using Progenesis QI v2.3 software, which performed peak alignment, peak picking, and deconvolution. Metabolite identification was conducted by comparing the data with information from internet sources such as Metlin, LIPID MAPS, and the Human Metabolome database.…”
Section: Untargeted Metabolomic Analysismentioning
confidence: 99%